Design School : Layout : a practical guide for students and designers - Poulin, Richard (Rockport Publishers, an imprint of The Quarto Group, 2018)
"Design School: Layout is an instructive guide for students, recent graduates, and self-taught designers. It provides a comprehensive introduction to creating and changing layouts: a crucially important skill that underpins practically every aspect of graphic design. You'll get in-depth analysis of all the major areas of theory and practice used by experienced professional designers. Each section provides explanation and visual examples of grid systems and in-depth discussion of compositional principles and strategies. The text is interspersed with tests designed to help you retain key points you've covered in the preceding spreads, and includes illustrations sections with real world scenarios. This in-depth guide avoids the temptation to stray into other areas of design technique, preferring to cover the essential, detailed skills of the professional graphic designer to arm you with the knowledge needed for a successful start to your chosen career."--